2017
DOI: 10.1016/j.placenta.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Syncytial nuclei accumulate at the villous surface in IUGR while proliferation is unchanged

Abstract: The data of the present study indicate a previously unknown type of regulation of syncytial stability and function, independent of proliferation. We hypothesize that in IUGR, post-proliferative trophoblast nuclei accumulate at the villous surface of peripheral villous branches. This could possibly reflect the presence of an unknown mechanism controlling syncytial function and stability by modulation of syncytial passage time rather than by modulation of proliferative supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 31 publications
0
12
1
Order By: Relevance
“…Proliferation in term human PE and IUGR placentas is well investigated, and it has been suggested that there is no change in trophoblast proliferation 70 , 71 , when evaluated at term. This supports our observations that in response to RUPP, we see no significant change at E18.5 in proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Proliferation in term human PE and IUGR placentas is well investigated, and it has been suggested that there is no change in trophoblast proliferation 70 , 71 , when evaluated at term. This supports our observations that in response to RUPP, we see no significant change at E18.5 in proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…non-proliferative) cell nuclei of villous trophoblast were subject to this effect, the unique bi-layered architecture of villous trophoblast as an epithelium comes into focus. It is clear that most of the PCNA-negative cell nuclei are part of the apical trophoblast layer, the syncytiotrophoblast 35,37 . Syncytiotrophoblast is the central tissue organizing materno-fetal transport and traffic 30 and the present study shows that this is the sexually dimorphic part of villous trophoblast.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of topologic orientation in 3D which is associated with 2D histology is especially relevant for tree structures which can only be fully interpreted in 3D. This shortcoming was overcome by the introduction of next-generation quantitative 3D histology of the human placenta, which guarantees instantaneous orientation in 3D and connects any identifiable structure like trophoblast cell nuclei to their 3D site of occurrence in the villous tree 35,36 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations